2013
DOI: 10.1002/dvdy.24030
|View full text |Cite
|
Sign up to set email alerts
|

TALE transcription factors during early development of the vertebrate brain and eye

Abstract: * Our brain's cognitive performance arises from the coordinated activities of billions of nerve cells. Despite a high degree of morphological and functional differences, all neurons of the vertebrate central nervous system (CNS) arise from a common field of multipotent progenitors. Cell fate specification and differentiation are directed by multistep processes that include inductive/external cues, such as the extracellular matrix or growth factors, and cell-intrinsic determinants, such as transcription factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 220 publications
(277 reference statements)
2
25
0
2
Order By: Relevance
“…We identified 5761 Pbx and 1410 Meis binding regions (1% IDR) enriched for consensus motifs that correlate with those previously identified in 11.5 day mouse embryos (Penkov et al 2013) ( Supplemental Table S5,6). The larger number of Pbx bound regions compared to Meis is consistent with its more general role as a cofactor for a variety of TFs (Laurent et al 2008;Schulte and Frank 2014). In comparing these genome-wide profiles with Hoxa1 bound regions, a large number also display co-occupancy of Pbx and Meis (Fig.…”
Section: Clustered Binding Sites For Hox Pbx and Meissupporting
confidence: 60%
“…We identified 5761 Pbx and 1410 Meis binding regions (1% IDR) enriched for consensus motifs that correlate with those previously identified in 11.5 day mouse embryos (Penkov et al 2013) ( Supplemental Table S5,6). The larger number of Pbx bound regions compared to Meis is consistent with its more general role as a cofactor for a variety of TFs (Laurent et al 2008;Schulte and Frank 2014). In comparing these genome-wide profiles with Hoxa1 bound regions, a large number also display co-occupancy of Pbx and Meis (Fig.…”
Section: Clustered Binding Sites For Hox Pbx and Meissupporting
confidence: 60%
“…The pervasive and dynamic expression of Pbx, Meis, and Prep genes in the mouse embryonic head, in domains patterned by Hox genes, and also in Hox-less territories (for reviews, see Alexander et al 2009;Schulte and Frank 2014) suggested critical roles for these TFs in brain and cranium development. Here we discuss three paradigmatic examples of PBX-depedent processes in head morphogenesis.…”
Section: Control Of Embryonic Development and Onset Of Disease Under mentioning
confidence: 99%
“…Thus, besides Ccnd1, Meis1 is likely to regulate additional neurogenic pathways. This regulation must take place via a Hox/Pbx-independent mechanism because Hox genes, which are well-known partners of Meis in the trunk, are not expressed in the head (Schulte and Frank, 2014). Furthermore, there is no indication that Pbx genes contribute to early eye formation, even though compound knockout mice have been generated and extensively studied (Capellini et al, 2011;Stankunas et al, 2008).…”
Section: Microphthalmia Is Not a Consequence Of Meis1 Function In Thementioning
confidence: 99%
“…Members of the Meis subfamily are however also expressed in the brain and sensory organs (Schulte and Frank, 2014), which are Hox-free embryonic regions (Duboule, 2007;Mallo and Alonso, 2013). In particular, Meis1 is expressed in the vertebrate forebrain and sensory organ primordia, including the eye, being essential for the specification of part of these structures.…”
Section: Introductionmentioning
confidence: 99%